Healing the Wound of Drug Abuse: Restorative Justice in Indonesian Narcotics Rehabilitation - Sagala, Bonni Ferdy; Akrial, Zul; Musa, M.; Zulkarnain, Zulkarnain (UIR Law Review, 2026)
Indonesian Law No. 35 of 2009 on Narcotics recognizes narcotics addicts as individuals entitled to medical and social rehabilitation rather than ordinary criminals, reflecting a shift from a punitive criminal justice model to a public health approach. The law promotes decriminalization of narcotics users and requires law enforcement to prioritize rehabilitation. However, in practice, many addicts continue to be arrested, prosecuted, and imprisoned alongside drug dealers, revealing a significant gap between legal norms and implementation. This study examines the implementation of rehabilitation through a restorative justice approach within the jurisdiction of the Rokan Hilir Resort Police and identifies the main obstacles affecting its effectiveness. Using a sociological juridical method with a descriptive analytical approach, the research analyzes empirical data from narcotics cases handled by the Rokan Hilir Police between 2021 and 2022. The findings indicate an increase in narcotics cases from 176 in 2021 to 187 in 2022, underscoring the need for effective rehabilitation-based interventions. Although Law No. 35/2009 and Police Regulation (Perpol) No. 8 of 2021 provide a legal framework for restorative justice and rehabilitation, implementation remains constrained by limited rehabilitation funding, social stigma, procedural difficulties in addiction assessment, and potential misuse of authority by law enforcement officers. The study highlights the persistent gap between rehabilitation-oriented legal norms and punitive enforcement practices and emphasizes the need for stronger institutional support to ensure that narcotics addicts receive recovery-oriented justice.